Low-carbon steel fatigue behavior after pack carburizing with buffalo bone charcoal and barium carbonate media - Bontong, Yafet; Rante, Milka; Nitha, Nitha (Politeknik Negeri Lhokseumawe, 2024)
The pack carburizing method is a technique that can be employed to enhance the surface hardness of Low-Carbon Steel (LCS). This method can potentially improve the hardness of the material while maintaining its strength. This study aims to investigate how different carburizing media, specifically varying percentages of Buffalo Bone Charcoal (BBC) powder as a carbon source, impact the mechanical properties of LCS. The temperature in the carburizing process ranges from 850°C and 950°C while maintaining a holding time of 2 hours. The carbon derived from buffalo bone charcoal is finely ground and mixed with barium carbonate (BaCO3) as the energizer during this process. This study used different ratios of BBC powder and BaCO3 as carburizing mediums. The ratios tested were 60% BBC + 40% BaCO3, 70% BBC + 30% BaCO3, and 80% BBC + 20% BaCO3, based on the weight of the BBC powder used in the carburizing process. The steel will be combined with BaCO3 and powdered BBC for this research. Next, the fatigue test was examined. BBC in the pack carburizing process increases LCS carbon content by 0.735% from 0.268%. This change alters the steel's microstructure, possibly increasing its hardness and wear resistance. The direct link between BBC concentration and LCS carbon enrichment shows the process's efficiency. Pack carburizing also improves LCS fatigue strength. This improvement is due to higher BBC concentration, smaller carburizing medium particles, and higher processing temperatures. After carburizing, the LCS can resist 36,625 to 61,435 cycles.